Corticolimbic connectivity as a possible biomarker for bipolar disorder. (June 2014) - Vai, Benedetta; Bollettini, Irene; Benedetti, Francesco
Abstract : Bipolar disorder is a severe, disabling and life-threatening illness, which affects nearly 2% of the general population. The identification of reliable and objective biomarkers may aid early diagnosis and optimize treatment efficacy. Through a careful overview of the neuroimaging studies which investigated the structural, functional, and effective connectivity in bipolar disorder, we explored the role of a disconnected cortico-limbic circuitry in the development and maintenance of the disorder. This review offers perspectives and suggestions for future research, in order to propose the corticolimbic disconnection as a neurobiological underpinning and biomarker for bipolar psychopathology.